C++ algorithms for digital signal processing - Embree, Paul M. (Prentice Hall, 1999)
Digital signal processing fundamentals - Programming fundamentals - User interface and disk storage routines - Filtering routines - Discrete Fourier Transform routines - Matrix and vector routines - Image processing routines - Appendices.